FEATURES AND ANALYSIS OF TEACHING ENGINEERING AND COMPUTER GRAPHICS USING THE AUTOCAD PROGRAM - F.A.Abdurakhimova (Bright Mind Publishing, 2025)
Graphic training of students in technical fields is the basis of engineering education. Changes in state educational standards have led to a revision of the content and teaching methods of these academic disciplines. Professional competencies of many disciplines require students to master computer graphics tools.
Keywords: AUTOCAD program, engineering and computer graphics, descriptive geometry, engineering graphics, discipline, approaches to the content of the discipline, teaching methods.